Chromosome-level genome assembly of the sweet potato rot nematode Ditylenchus destructor - Yiwei Yang; Ruirui Feng; Bo Hong; Yuchuan Fang; Chen Liu; Kui Wang; Deliang Peng; Yingmei Li; Huan Peng; Qing Chang (Scientific Data)
Abstract Ditylenchus destructor, commonly known as the potato rot nematode, is a significant plant-parasitic pathogen affecting over 120 plant species globally. Effective control measures for D. destructor are limited, underscoring the need a high-quality reference genome to understand its pathogenic mechanisms. Herein, we combined Illumina short reads, PacBio long reads, and Hi-C mapping technology to construct a chromosome-scale reference genome assembly for D. destructor. The genome assembly totals 133.86 Mb, with 129.51 Mb (96.74%) of sequences anchored onto 4 pseudo-chromosomes, achieving a scaffold N50 of 32.25 Mb. The assembled genome contains 28.14% repeat sequences and identifies 19,165 protein-coding genes, of which 18,444 (96.24%) are functionally annotated. The genome assembly demonstrates a high level of completeness, with 73.8% complete the nematoda-specifc Benchmarking Universal Single-Copy Orthologs (BUSCO) genes, significantly higher than that of other reported plant-parasitic nematode genomes. This high-quality reference genome will serve as a valuable genomic resource for future research aimed at understanding the pathogenesis of D. destructor and developing effective control strategies.